Triboelectric vibration sensor for a human-machine interface built on ubiquitous surfaces. (May 2019) - He, Qiang; Wu, Yufen; Feng, Zhiping; Sun, Chenchen; Fan, Wenjing; Zhou, Zhihao; Meng, Keyu; Fan, Endong; Yang, Jin
Abstract: Human-machine interfaces enable the exchange of information between people and machines, which plays a crucial role in artificial intelligence. In this field, sensors based on magnetism, electricity, mechanics, and optics are used to construct interactive interfaces and have an important role in sensing human behavior. Here, we present a vibration sensor based human-machine interface (HMI) with an unlimited sensing area on a ubiquitous surface by detecting and positioning an external vibration source. To accurately perceive an external minute vibration, we proposed triboelectric vibration sensors (TVS) designed by mimicking the ampulla in the lateral line of a fish. Imitating the cilia wrapped in the ampulla structure, the tribo-pair of TVS were designed as nanowire arrays and hemispherical pore structures. It achieved a high force sensitivity of 0.97 V/N when the force is less than 1 N and a broad frequency range from 1 to 3 kHz. Given the excellent performance of the TVS, an in-plane vibration source detection and location system was developed, which utilizes the time difference in the arrival estimation method based on correlation analysis. As a demonstration, a TVS-based intelligent virtual digital keyboard was developed by sensing and locating the position of the keystroke for interactive input and importer authentication according to the bionic features. Furthermore, a customized multifunctional desktop interactive system was established by functionalizing an ordinary table for convenient electrical appliance control. In this way, ordinary surfaces such as tables, walls, and doors have the potential to be converted into multifunctional interactive interfaces. The proposed TVS-based HMI in this work can be immediately and extensively adopted in a variety of applications for portable computer peripherals, cyber security, and intelligent home systems. Graphical abstract: Human-machine interfaces enable the exchange of information between people and machines, which plays a crucial role in artificial intelligence. In this study, a triboelectric vibration sensor (TVS) based human-machine interface with an unlimited sensing area was developed on a ubiquitous surface. Imitating the cilia wrapped in the ampulla structure in the lateral line of a fish, the TVS was designed as hierarchical structure with nanowire arrayed and hemispherical porous tribo-pair and achieved a high vibration sensing performance. Moreover, by locating/positioning the tapping/knocking point on TVS mounted surface, a TVS-based intelligent digital keyboard and a customized multifunctional desktop interactive system were developed for interactive input and smart home.Image 1 Highlights: Attribute to the elegant hierarchical structure of the TVS mimicked the ampulla in lateral line of a fish, a high pressure sensitivity of 0.97 V/N, a broad frequency range from 1 to 3 kHz, and a minimum detection of 0.01 N had been achieved. Enable it to perceive minute vibration caused by tapping/knocking. By locating/positioning the tapping/knocking point on TVS mounted surface, ubiquitous daily surfaces can be converted to an intelligent sensing interface. A vibration-based human-machine interface can be established by properly placing TVS on daily surfaces such as desktop and wall. Compared with the traditional touch screen which can only be in the area of sensors, the sensing area in this work is vastly expanded. A TVS-based intelligent virtual digital keyboard and a customized multifunctional desktop interactive system were developed for interactive input and smart home. Specially, the identities of the importers using the intelligent digital keyboard can be authenticated by the bionic features extracted from the vibration signals.